Digital transformation and its role in the quality of the educational process for primary school teachers in the city of Riyadh - Hamdi, Rahaf Ali; Al-Bishr, Saud Ghassan (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the reality of digital transformation and its role in improving the quality of the educational process for female teachers at the primary stage in the city of Riyadh, and to know the reality of digital infrastructure and resources and the challenges that limit the digital transformation process. The research used the descriptive analytical method. The questionnaire was adopted as a tool to collect the data necessary for the study, and the study sample consisted of 180 female teachers at the primary level in the city of Riyadh. After conducting the necessary statistical analysis, the study reached several results, the most important of which is: that there is an effective system for protecting digital data used in the educational process. Teachers are also trained on the use of technology on a regular basis. The weakness of Internet networks affects the quality of digital education. Considering these results, the researcher presented a set of recommendations, including developing continuous training programs for teachers. Improving technological infrastructure. In addition to enhancing cooperation with experts in the field of educational technology.
Keywords: digital transformation; quality of the educational process